Big Data and Digitization Integration: Between Benefits and Risks (Journal of Economic Additions, 2019)
Big data a technological pillar of real-time access to giant digital databases. It is also a dual technical system that does not derive rules from all technologies; it brings financial benefits but can also generate remarkable disadvantages. Being a complex polymorphic object, no precise or universal definition can be fixed to Big Data. The article summarizes a literature review of the concept on the one hand, and to assess the integration of digitization in economic activities in Algeria on the other hand, which however represents a weak dynamic in the field of This is mainly due to a significant lack of support and funding mechanisms, as well as a weak development of innovation activities.Key words: Big Data, Digitization, Accompanying Devices, Innovation, ICT.Jel Classification: L86, L84, M55, O32, O14.